Geography of opportunity: a multilevel analysis of regional and school-level inequities in Somaliland’s educational outcomes - Cumar, Mukhtaar Axmed; Abdi, Mustafe Khadar; Ali, Tawakal Abdi; Muse, Abdisalam Hassan; Adem Abdulahi, Bahir; Ali, Jibril Abdikadir (Frontiers in Education, 2025)
Persistent regional and school-level inequities continue to shape students’ educational outcomes in Somaliland. Despite policy advances, empirical evidence quantifying how much variation in academic achievement is attributable to individual, school, and regional factors remains limited. This study applies the geography of opportunity framework to investigate how location and institutional context influence student performance across Somaliland’s secondary schools. A cross-sectional multilevel analysis was conducted using a comprehensive administrative dataset from the Somaliland National Examination and Certification Board (SLNECB), comprising 505,398 subject-level grade records from 186 secondary schools (2020-2023). Using linear mixed-effects models estimated in R (lme4), students (Level 1) were nested within schools (Level 2). Three models were fitted: a null model, a random intercept model (including sex, subject, and year as fixed effects), and a random slope model allowing the effect of sex to vary by school. Model comparison was based on AIC, BIC, and marginal/conditional R2 values. The Intraclass Correlation Coefficient (ICC = 0.234) indicated that 23.4% of total variance in student grade points stemmed from school-level factors, revealing a strong “school effect.” The random slope model demonstrated the best fit (AIC = 1,587,694.8; BIC = 1,587,895.2; R2_conditional = 0.348). Performance varied markedly across subjects: Mathematics (d = −0.73) and Chemistry (d = −0.66) showed the largest deficits, while History (d = +0.39) performed highest. Although the overall sex difference was trivial (d = 0.02), the effect varied significantly between schools. A negative correlation (r = −0.35) between school intercepts and gender slopes indicated that higher-performing schools reduced or reversed gender gaps. Results reveal a deeply unequal educational landscape in Somaliland where student achievement is strongly conditioned by school context. The substantial between-school variance confirms that location and institutional quality, rather than individual characteristics, are primary drivers of inequality. Strengthening underperforming schools—especially in regions such as Sool, Togdheer, and Xaysimo—and investing in STEM teaching capacity are crucial for equity. The findings underscore the importance of geographically targeted policies and reinforce that enhancing school quality also promotes gender equity.